Characterization of methane hydrate extraction influenced by hydraulic fractures using a coupled thermo-hydro-mechanical-chemical model - Sun, Hao; Xu, Xiangyu; Jia, Chao (Frontiers in Earth Science, 2024)
The low permeability of the methane hydrate-bearing sediment limits the methane gas extraction. To enhance the methane hydrate extraction, hydraulic fracturing can be a promising approach to improve the hydrate reservoir permeability by creating a fracture network in the reservoir. In this study, a coupled thermo-hydro-mechanicalchemical mathematical model and its numerical implementation based on finite element technology are introduced to analyze the methane hydrate extraction through fractured methane hydrate-bearing sediment considering methane hydrates dissociation, gaswater two-phase flow, heat transfer, dynamic changes of the sediment permeability and deformation of both sediment matrix and fractures as well as capturing the interplay between them. The coupled thermo-hydro-mechanical-chemical numerical model is